KREDIBILITAS PENDETA PADA SAAT BERKHOTBAH DI GEREJA SIDANG JEMAAT ALLAH “KALVARI” PALU - Kristi, Felicia (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2020)
In every religion, both organizations and individuals who have been recognized can play a role in the continuity of religious activities which we generally know as Religious Leaders. Specifically in the Christian religion, they are referred to as priests. The pastor has a very important role in the ongoing worship activities in the church, therefore the pastor is indirectly required to be able to guide the congregation he leads in one way, namely delivering sermons to the congregation well and having credibility, because of the credibility he has. So a pastor can convince and influence his congregation with the quality, capability, or strength to inspire trust. The credibility of the communicator is divided into two aspects, namely the credibility of expertise and the credibility of trust. The aim of this research is to determine the credibility of the pastor when preaching in the eyes of the congregation of the Kalvary Assemblies of God Church in Palu. The research method used is a descriptive method with the principle of a survey approach, namely critical observation or investigation to obtain permanent information regarding a particular problem and object, in a particular community group area or location that will be studied. The results of the research show that all the pastors at the Assemblies of God Church